2009
DOI: 10.1002/smll.200800690
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Epitaxial InAs Nanowires on GaAs (111)B

Abstract: The evolution of InAs nanowires on the GaAs (111)B substrate by metal–organic chemical vapor deposition shows that InAs traces are formed and elongated first, driven by the liquid Au catalysts preferentially retaining interfaces with the GaAs substrate due to the Au/GaAs interfacial energy being lower than that of Au/InAs. Vertical InAs nanowires initiate when elongated traces intersect (see image).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 24 publications
3
57
1
Order By: Relevance
“…Our extensive TEM investigations showed that over 95% observed nanowires were associated Au sliding. As demonstrated in our earlier studies, 10,13 Au catalysts prefer to retain interfaces with GaAs and this drives the downward growth of InAs nanowires led by the Au catalysts. This growth behavior of InAs is indicated by an arrow in Fig.…”
Section: Methodssupporting
confidence: 63%
“…Our extensive TEM investigations showed that over 95% observed nanowires were associated Au sliding. As demonstrated in our earlier studies, 10,13 Au catalysts prefer to retain interfaces with GaAs and this drives the downward growth of InAs nanowires led by the Au catalysts. This growth behavior of InAs is indicated by an arrow in Fig.…”
Section: Methodssupporting
confidence: 63%
“…3. In the part (a), since there exists a 4.2% difference in the lattice parameters between GaAs (aGaAs¼0.565 nm) and InP (aInP ¼0.587 nm), there will be many {111} type microtwins and stacking faults parallel to the InP/GaAs interface when InP nucleate on GaAs buffer layers (labeled by a dot line in InP nanowires) [14]. These twins/stacking faults can relieve misfit strain between InP and GaAs, which is caused by the formation of a/6 〈112〉 type partial dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…However in this sample, a [1 À 12] direction InP nanowire was observed. There will be many {111} type microtwins and stacking faults parallel to the InP/GaAs interface when InP nucleate on GaAs buffer layers [14]. Those dislocations can effectively reduce the strain energy of InP crystal and make it easier growth aligned in 〈1 À12〉 directions.…”
Section: Resultsmentioning
confidence: 99%
“…1(c) is a SEM back-scattered electron image and reveals the presence of particles with heavier element(s) at the tip of lateral nanowires, which should be the Au catalysts we used to induce the nanowire growth. 24 Figure 1(d) is a schematic diagram to illustrate our observation of the simultaneously grown free-standing and lateral nanowires.…”
mentioning
confidence: 99%
“…During annealing, surface As atoms may evaporate, leaving behind more free Ga atoms to form an alloy with the Au particles. 31 Since the interfacial energy of Au-Ga particle has a minimum with GaAs {111} planes, 24,32 the particle dissolves the original (001) surface, and forms a pit with four {111} planes of the GaAs substrate with ð 1 11Þ and (111) (belonging to {111} A planes -the red planes in Fig. 4); and ð 111Þ and ð1 11Þ (belonging to {111} B planesthe green planes in Fig.…”
mentioning
confidence: 99%